Design and manufacture of mechanical drive systems for road sweepers on flat surfaces - Iqbal Raihan; Mirzal Lubis; Ahmad Marabdi Siregar; Chandra A Siregar; Affandi (JTTM : Jurnal Terapan Teknik Mesin, 2024)
The sweeper works by utilizing pushing force because it does not use a motor, so it is environmentally and energy friendly. The manufacturing and assembly process is carried out after all machine components are made according to the designed sizes. The working principle of this machine is that the wheel is the driving source using a gear and chain transmission. The driving source for the directional broom is located on the left side of the wheel, using an umbrella gear to change the direction of rotation of the broom to the opposite direction. Meanwhile, for the distribution broom, the driving source is located on the right side of the wheel. By using two gears that touch each other and the difference in the number of teeth, namely three to one, can produce a fast sweeping speed. The function of the directional broom is to direct rubbish that is in the corners of walls or rooms to the middle of the machine. Meanwhile, the function of the distribution broom is to distribute waste to the tub which has been directed by the guide broom towards the middle of the machine. After testing, it turned out that this sweeping machine can optimally pick up all the rubbish on a flat surface along with the dust. The results of the design of this machine have been able to produce very good performance, apart from saving time it also produces fairly clean sweeping results